A Simple Clinical Measure of Quadriceps Muscle Strength Identifies Responders to Pulmonary Rehabilitation - James R. Walsh; Norman R. Morris; Zoe J. McKeough; Stephanie T. Yerkovich; Jenny D. Paratz (Pulmonary Medicine)
The aim was to determine if baseline measures can predict response to pulmonary rehabilitation in terms of six-minute walk distance (6MWD) or quality of life. Participants with COPD who attended pulmonary rehabilitation between 2010 and 2012 were recruited. Baseline measures evaluated included physical activity, quadriceps strength, comorbidities, inflammatory markers, and self-efficacy. Participants were classified as a responder with improvement in 6MWD (criteria of ≥25 m or ≥2SD) and Chronic Respiratory Questionnaire (CRQ; ≥0.5 points/question). Eighty-five participants with a mean (SD) age of 67(9) years and a mean forced expiratory volume in one second of 55(22)% were studied. Forty-nine and 19 participants were responders when using the 6MWD criteria of ≥25 m and ≥61.9 m, respectively, with forty-four participants improving in CRQ. In a regression model, responders in 6MWD (≥25 m criteria) had lower baseline quadriceps strength (P=0.028) and higher baseline self-efficacy scores (P=0.045). Independent predictors of 6MWD response (≥61.9 m criteria) were participants with metabolic disease (P=0.007) and lower baseline quadriceps strength (P=0.016). Lower baseline CRQ was the only independent predictor of CRQ response. A participant with relatively lower baseline quadriceps strength was the strongest independent predictor of 6MWD response. Metabolic disease may predict 6MWD response, but predictors of CRQ response remain unclear.